Potentials of Cellular Reprogramming as a Novel Strategy for Neuroregeneration - Fang, Lyujie; El Wazan, Layal; Tan, Christine; Nguyen, Tu; Hung, Sandy S. C.; Hewitt, Alex W.; Wong, Raymond C. B. (Frontiers in Cellular Neuroscience, 2018)
Cellular reprogramming technology holds great potential for tissue repair and regeneration to replace cells that are lost due to diseases or injuries. In addition to the landmark discovery of induced pluripotent stem cells, advances in cellular reprogramming allow the direct lineage conversion of one somatic cell type to another using defined transcription factors. This direct reprogramming technology represents a rapid way to generate target cells in the laboratory, which can be used for transplantation and studies of biology and diseases. More importantly, recent work has demonstrated the exciting application of direct reprogramming to stimulate regeneration in vivo, providing an alternative approach to transplantation of donor cells. Here, we provide an overview of the underlying concept of using cellular reprogramming to convert cell fates and discuss the current advances in cellular reprogramming both in vitro and in vivo, with particular focuses on the neural and retinal systems. We also discuss the potential of in vivo reprogramming in regenerative medicine, the challenges and potential solutions to translate this technology to the clinic.